Evaluation of pathological complete response rates in breast cancer patients undergoing neoadjuvant therapy - Gabriella Ferezini Oliveira de Sá; Pedro Vilar de Oliveira Villarim; Pedro Hortêncio Saboia da Escossia Melo; Ayane Cristine Alves Sarmento; Ana Katherine Gonçalves; Kleyton Santos de Medeiros; Cristina Rocha de Medeiros Miranda (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: This study aims to assess the rate of pathological complete response (pCR) in breast cancer patients undergoing neoadjuvant therapy and to explore its correlation with clinical, molecular, and prognostic factors. Methods: We conducted this retrospective observational study at Liga Contra o Câncer, a major public oncology reference center in Northeast Brazil. We included patients diagnosed with breast cancer who initiated neoadjuvant therapy between June 2018 and June 2019. Patients with a history of recurrent breast cancer or those who did not undergo surgery were excluded. The primary outcome was the pCR rate, with secondary outcomes including Overall Survival (OS), Disease-Free Survival (DFS), mortality, and disease recurrence. Follow-up extended until August 2022. We performed multivariate Cox regression analysis to correlate outcomes with predetermined variables. Results: Of the 292 included patients, 63 (21.6%) achieved pCR. The mean follow-up duration was 42.8 months. Multivariate logistic regression analysis revealed an association between pCR and the AC-TH regimen [OR = 2.4; 95%CI = 1.13 - 5.24; p=0.023], as well as between pCR and HER2-positive tumors [OR 2.49; 95% CI = 1.14 - 5.86; p=0.028]. Complete pathological response was associated with higher DFS [HR 0.33; 95%CI 0.13-0.86; p=0.024]. Conclusion: Neoadjuvant therapy demonstrated significant efficacy in achieving pathological response in breast cancer patients. We observed a strong association between the AC-TH regimen, HER2-positive status, and pCR.